2020
DOI: 10.1002/cbic.201900740
|View full text |Cite
|
Sign up to set email alerts
|

General Principles for Yield Optimization of Nucleoside Phosphorylase‐Catalyzed Transglycosylations

Abstract: The biocatalytic synthesis of natural and modified nucleosides with nucleoside phosphorylases offers the protecting‐group‐free direct glycosylation of free nucleobases in transglycosylation reactions. This contribution presents guiding principles for nucleoside phosphorylase‐mediated transglycosylations alongside mathematical tools for straightforward yield optimization. We illustrate how product yields in these reactions can easily be estimated and optimized using the equilibrium constants of phosphorolysis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 17 publications
7
68
0
4
Order By: Relevance
“…Transglycosylation reaction to produce dihalogenated purine nucleosides using thermostable nucleoside phosphorylases as biocatalysts and uridine (1a) and thymidine (1b) as sugar donors. To efficiently produce 2a-and 2b-containing nucleosides in a transglycosylation reaction, equilibrium state thermodynamic calculations were carried out [13]. We have recently shown that nucleoside phosphorolysis is a reversible endothermic reaction under tight thermodynamic control [14].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Transglycosylation reaction to produce dihalogenated purine nucleosides using thermostable nucleoside phosphorylases as biocatalysts and uridine (1a) and thymidine (1b) as sugar donors. To efficiently produce 2a-and 2b-containing nucleosides in a transglycosylation reaction, equilibrium state thermodynamic calculations were carried out [13]. We have recently shown that nucleoside phosphorolysis is a reversible endothermic reaction under tight thermodynamic control [14].…”
Section: Methodsmentioning
confidence: 99%
“…* Experiments were performed with 5 mM nucleobase, 5 mM sugar donor 1a or 1b, and 2 mM potassium phosphate buffer at 40 • C to determine the equilibrium constants. ** Equilibrium constants of phosphorolysis of the target compounds were calculated as described in [13]. Known equilibrium constants for these sugar donors at 40 • C were employed for the calculations [14].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations